Changes in peripheral refraction, higher-order aberrations, and accommodative lag with a radial refractive gradient contact lens in young myopes - Pauné, Jaume (2016)
Purpose: To evaluate changes in the peripheral refraction (PR), visual quality, and accommodative lag with a novel soft radial refractive gradient (SRRG) experimental contact lens that produces peripheral myopic defocus. Methods: 59 myopic right eyes were fitted with the lens. The PR was measured up to 30° in the nasal and temporal horizontal visual fields and compared with values obtained without the lens. The accommodative lag was measured monocularly using the distance-induced condition method at 40 cm, and the higher-order aberrations (HOAs) of the entire eye were obtained for 3- and 5-mm pupils by aberrometry. Visual performance was assessed through contrast sensitivity function (CSF). Results: With the lens, the relative PR became significantly less hyperopic from 30° to 15° temporally and 30° nasally in the M and J0 refractive components (P,0.05). Cylinder foci showed significant myopization from 30° to 15° temporally and 30° to 25° nasally (P,0.05). The HOAs increased significantly, the CSF decreased slightly but reached statistical significance for 6 and 12 cycles per degree (P,0.05), and the accommodative lag decreased significantly with the SRRG lens (P¼0.0001). There was a moderate correlation between HOAs and CSF at medium and high spatial frequencies. Conclusion: The SRRG lens induced a significant change in PR, particularly in the temporal retina. Tangential and sagittal foci changed significantly in the peripheral nasal and temporal retina. The decreased accommodative lag and increased HOAs particularly in coma-like aberration may positively affect myopia control. A longitudinal study is needed to confirm this potential.